Innovative numerical method for solving heat conduction using subdivision collocation (Mar, 10.1007/s12190-025-02429-9, 2025) - Malik, Safia; Ejaz, Syeda Tehmina; Rezapour, Shahram; İnç, Mustafa; Mustafa, Ghulam (Springer Heidelberg, 2025)
[Abstract Not Available]